Fiqh of Civilization in Building a Legal State: The Relevance of Muhammad Arkoun's Thought - Latif, Mukhlis; Mutawalli, Muhammad (Faculty of Sharia and Law, Universitas Islam Negeri (UIN) Walisongo Semarang, 2023)
Arkoun's political concept is very relevant to the expected idea of civilizational fiqh to resolve social problems nationally and internationally. The purpose of this article is to discuss the fiqh of civilization as an element of the rule of law which is connected with the political thought of state administration Muhammad Arkoun which is based on Islamic values in a legal state. Fiqh of civilization is a major breakthrough in building a legal state in analyzing current problems in the country and the world. This research uses the method qualitative with a conceptual approach by applying and studying thinking Muhammad Arkoun about the political concept of state administration based on values Islam through his works. This research contains the concept of political state; Muhammad Arkoun emphasized the importance of broadening the view of sources of Islamic law and contextual interpretation of Islamic law. Arkoun emphasized that state politics in Islam is more focused on the unity of the people, including religion and state. This aspect is currently being developed through fiqh concepts of civilization. Arkoun's critical thinking can help face the challenges of modernization and globalization in the Islamic world, which are reviewed in building a legal state according to the concept of Islamic statecraft.